2014
DOI: 10.1002/cam4.352
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a modified clinical risk score to predict cancer‐specific survival for stage II colon cancer

Abstract: Many patients with stage II colon cancer will die of their disease despite curative surgery. Therefore, identification of patients at high risk of poor outcome after surgery for stage II colon cancer is desirable. This study aims to validate a clinical risk score to predict cancer-specific survival in patients undergoing surgery for stage II colon cancer. Patients undergoing surgery for stage II colon cancer in 16 hospitals in the West of Scotland between 2001 and 2004 were identified from a prospectively main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…It is of interest to compare this to previous work in our geographical area that has identified that age and emergency presentation are associated with survival in Stage II disease [25]. In the present study when adjusted for the SIR, as evidenced by mGPS, emergency presentation failed to retain prognostic significance.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…It is of interest to compare this to previous work in our geographical area that has identified that age and emergency presentation are associated with survival in Stage II disease [25]. In the present study when adjusted for the SIR, as evidenced by mGPS, emergency presentation failed to retain prognostic significance.…”
Section: Discussioncontrasting
confidence: 42%
“…For example, several large prospective cohort studies have identified inflammatory mediators including as CRP and albumin, as being predictive of both all-cause, cancer-specific mortality and cardiovascular mortality in the over 50s [23,24]. It is of interest to compare this to previous work in our geographical area that has identified that age and emergency presentation are associated with survival in Stage II disease [25]. In the present study when adjusted for the SIR, as evidenced by mGPS, emergency presentation failed to retain prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high clinical heterogeneity of CC, the conventional clinical features including the current American Joint Committee on Cancer (AJCC) staging, Tumor, Nodal Involvement, Metastasis (TNM) staging, and grade are insufficient for accurately predicting individualized prognosis (8)(9)(10)(11). Therefore, it is essential to establish novel and robust prognostic biomarker signatures to identify the molecular changes that can reliably estimate clinical outcomes of CC patients, which would have tremendous value of guiding appropriate individualized clinical managements and treatments for CC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Ten studies had multivariate HR of CSS [16,18,20,27,36,40,62,65,73,80] . AL was associated with a decreased CSS (HR 1.65 95% CI 1.13-2.42, p < 0.0001) (Figure S5).…”
Section: Cancer Speci C Survivalmentioning
confidence: 99%